FACULTY RESPONSIBILITY WITH RESPECT TO CORRECTING CERTAIN DEFECTS IN THE ACCOUNTANT'S EDUCATION. - Ray, Delmas D. (The Accounting Review, 1957)
Abstract 1. There is evidence that accounting graduates are often lacking in the breadth arid depth of training considered by employers, the Standards Rating Committee, and The Commission on Standards to be necessary for long-run success in accounting careers. 2. Since education is a life-time process, the first step in improving the accountant's education should be the ascertaining of what can best be done in the classroom and what can best be left until after graduation. 3. In the broader aspects of the student's training, our responsibility is primarily that of counselor to the student. 4. In education for business, the role of accounting faculties is that of showing how accounting fits into the economic frame- work, in reconciling and contrasting various points of view, and in assisting the student in viewing his knowledge of the various business specialties as a whole. 5. In education in accounting, there is need for much soul-searching relative to the present content of our accounting courses. Much more attention should be devoted to instilling into the student a consciousness of what constitutes professional conduct. To the extent that present textbooks are any criterion of the depth and breadth of accounting courses, we are lagging far behind the objectives set for us by employers, the Standards Rating Committee, and The Commission on Standards. We have an immediate responsibility to bring these texts more nearly in line with our avowed goals. In conclusion, the Standards Rating Committee and The Commission on Standards have gone on record as stating that the type of training needed for present-day accounting cannot be accomplished within a four-year curriculum. As we move toward longer periods of normal education, we can no longer use lack of time as an alibi for the shortcomings of our product.